The Role of Knowledge Sharing, Job Involment and Individual Innovation Capability on Employee Performance at PT. Bhirowo Jaya Mojokerto - Elok Cahyaning Pratiwi; Trijadi Herdajanto; Fajar Budiyanto; Zenita Afifah Fitriyani; Ulfa Rahmawati; Elia sjachriatin (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The aim of this study was to examine how individual innovation capability, job involvement, and knowledge sharing affect employee performance. Design/methodology/approach: A questionnaire with 65 employees of PT. Birowo Jaya as respondents provided the primary data for this investigation. Purposive sampling was the method of sampling employed in this investigation. Using route analysis, validate this research. Findings: The study's findings indicate that: (1) knowledge sharing positively impacts employee performance; (2) individual innovation capability positively impacts employee performance; (3) job involvement positively impacts employee performance; and (4) knowledge sharing, individual innovation capability, and job involvement positively impact employee performance simultaneously. Paper type: Research paper